A Measure of Fairness: The Economics of Living Wages and Minimum Wages in the United States - Osberg, Lars (Labour / Le Travail, 2009)
This article reviews the book, "A Measure of Fairness," by Robert Pollin, Mark Brenner and Jeannette Wicks-Lim.
Keywords: BOOKS – Reviews; BRENNER; Mark; Book reviews; Business And Economics–Labor And Industrial Relations; History–History of North And South America; LUCE; Stephanie; Labor economics; MEASURE of Fairness: The Economics of Living Wages & Minimum Wages in the United States; A (Book); Minimum wage; Nonfiction; POLLIN; Robert; United States; WICKS-Lim; Jeannette; Wage price policy; Wages